Strength of Cockle Shell Foam Concrete-Filled Hollow Added Steel Fibre - Suhaimi, Haziq Hafiez; Abd Rahman, Norashidah (Recent Trends in Civil Engineering and Built Environment, 2025)
Steel hollow sections are popular in construction due to their superior structural performance and versatility. However, conventional concrete infill presents challenges. This study focuses on the behaviour of concrete-filled steel hollow sections, specifically examining six specimens through axial compression tests. Half of the specimens were unfilled steel hollow sections, while the other three were filled with a blend of cockle shell foam concrete and steel fibre. The investigation aimed to evaluate the compressive strength of cockle shell foam concrete with added steel fibre, conducting cube tests at 7, 14, and 28 days. Results indicated a progressive increase in compressive strength with longer curing periods, with significantly higher strength observed at 28 days compared to 7 and 14 days. The axial compression test results suggest that incorporating cockle shell foam concrete and steel fiber enhances the strength of hollow sections under axial loads, surpassing the strength of unfilled steel hollow sections. Additionally, a distinct failure mode was observed during axial load testing for the unfilled steel hollow section, occurring consistently at both the top and bottom of the column. Overall, these findings provide valuable insights into the performance of cockle shell foam concrete with steel fiber in enhancing the compressive strength of concrete-filled steel hollow sections.